Effect of interaction strategy instruction on learner engagement in peer interaction. (July 2020) - Dao, Phung
Abstract: This study investigated the effect of interaction strategy instruction on learner engagement in peer interaction. The instruction was designed based on previous strategy training models, including five stages: Preparation (raising awareness of collaboration and interaction strategies), Presentation (presenting and analysing strategies), Practice (applying strategies in interaction), Self-evaluation (self-evaluating and reflecting on strategy use), and Expansion (continuing practising strategies). Fifty-six EFL learners ( M age  = 15.57, SD  = 3.35) were divided into two equal groups ( n = 28 in each), with only the treatment group receiving the interaction strategy instruction. Scores for learner engagement, gauged by multiple measures (idea units, LREs, instances of talk encouragement, reflection/development of ideas, enjoyment time and reported emotion), were compared from pre-to post-test and between the two groups. The results showed that interaction strategy instruction promoted greater generation of idea units, LREs, instances of talk encouragement and reflection, and positive emotion in both tasks. However, factors such as task features, perceptions of peers, and proficiency affected the learners' use of strategies. Learners also rated highly the usefulness of interaction strategy instruction for promoting effective interaction. The results indicate the benefits of interaction strategy instruction for enhancing the quality of peer interaction.